Vascular complications post invasive cardiovascular procedures - Newary, Yola; Kurnianingsih, Novi (Universitas Brawijaya, 2025)
Vascular complications following intracoronary or intracardiac surgeries, such as hematoma, pseudoaneurysm, and arteriovenous fistula, significantly contribute to morbidity and occasionally. Furthermore, these complications not only escalate treatment costs but also prolong hospital stays. Several risk factors have been associated with vascular issues post-coronary procedures, including prolonged femoral sheath use, excessive anticoagulation, multiple interventions during a single admission, catheter placement in the superficial or deep femoral artery, larger catheter sizes, and complex procedures such as atherectomy or stent placement. Strategies to mitigate procedural risks, ensure early detection of vascular injuries, and facilitate timely management can prevent long-term disabilities.